Produção e caracterização de redes de Bragg no visível gravadas por pulsos de femtossegundos em 248 nm - Sualehe, Ivenso da Silva Vasco (2016)
In this work, a visible wavelength fiber Bragg gratings (FBGs) were produced using ultrafast laser pulses adjusted with an OPO (optical parametric oscillator) to 248 nm UV femtosecond laser source. For that purpose it was employed the normal phase-mask method and different fibers loaded with hydrogen previously, in order to increase its photosensitivity. During de process the spectral characteristics were analyzed in terms of reflection as well as temperature and longitudinal deformations were made to analyze the post inscription main parameters of sensitivity comparing with IR spectral range produced FBGs.